Digital PCR Detection of mtDNA/gDNA Ratio in Embryo Culture Medium for Prediction of Embryo Development Potential - Zhang Q; Ji H; Shi J; Wang L; Ding L; Jiang Y; Huang X; Qiu Snr P; Li P (Dove Medical Press, 2021)
Qing Zhang,1,2 Hong Ji,1,2 Jian Shi,1,2 Longmei Wang,1,2 Lu Ding,1,2 Yufei Jiang,1,2 Xianjing Huang,1,2 Pingping Qiu Snr,1,2 Ping Li1,2 1Department of Reproductive Medicine, Women and Children’s Hospital Affiliated to Xiamen University, Xiamen, Fujian, People’s Republic of China; 2Xiamen Key Laboratory of Reproduction and Genetics, Xiamen, Fujian, People’s Republic of ChinaCorrespondence: Pingping Qiu; Ping LiDepartment of Reproductive Medicine, Women and Children’s Hospital Affiliated to Xiamen University, Zhenhai Road 10, Xiamen, Fujian, 361003, People’s Republic of ChinaTel +86-592-2663987Fax +86-592-2662032Email Pingingqiu826@163.com; saarc2001@sina.comPurpose: The ratio of mitochondrial DNA to genomic DNA (mtDNA/gDNA) in embryo culture medium as a predictor of embryonic development is a new method of noninvasive embryo screening. However, current tests based on this concept have proven inconsistent. The aim of this study was to define the predictive value of the ratio of mtDNA/gDNA for embryonic developmental potential.Materials and Methods: We used digital PCR to measure mtDNA/gDNA ratios in day 3 culture media of 223 embryos from 56 patients. We compared the relationship between the predictive value of mtDNA/gDNA ratio and each of embryo fragmentation, embryo morphological grade, and blastocyst formation.Results: mtDNA/gDNA ratio decreased significantly with a decrease in embryo rating: 22.54 (44.66); 31.25 (36.97) and 46.33 (57.11); Grades A vs C, P = 0.006; B vs C, P = 0.015. mtDNA/gDNA ratio increased overall with an increase in embryo fragment content but did not differ significantly between high-, -medium, and poor-quality embryos. Interestingly, this trend differed from that of the unformed blastocysts. mtDNA/gDNA ratio of cleavage stage embryos forming blastocysts was lower (P=0.005). Trends of mtDNA/gDNA ratio differed according to inner cell mass (ICM) and trophectoderm (TE) levels, but not significantly. mtDNA/gDNA ratio in day 3 culture medium was not significantly improved over morphological scores.Conclusion: We hereby show the correlation of mtDNA/gDNA ratio in the culture medium of developing embryos. The correlation between the mtDNA/gDNA ratio and early embryonic development was controversial. Furthermore, an increase in mtDNA/gDNA ratio might indicate reduced development potential, but the difference remains insufficient for application as a clinical predictor.Keywords: mtDNA/gDNA, embryo, digital PCR, blastocyst